1978
DOI: 10.1016/0022-3697(78)90059-8
|View full text |Cite
|
Sign up to set email alerts
|

Small-polaron mobility in nonstoichiometric cerium dioxide

Abstract: The high temperature drift mobility (ad) of charge carriers in nonstoichiometric cerium dioxide (CeOz_,X) has been calculated by combining the electrical conductivity and nonstoichiomet~ data on the basis of the oxygen vacancy model with correct ionization state. The electrical conductivity was measured by a four-probe d.c. technique and the nonstoichiometry by thermogravimetric analysis. The dilute solution model of the point defects is valid up to x = 0.03. From the magnitude of pd and its temperature depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
88
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(108 citation statements)
references
References 15 publications
18
88
0
Order By: Relevance
“…These values are in good agreement with literature values for small polaron migration in other ceria systems. 19,49,50 The pre-exponential factors show a decreasing tendency with decreasing Pr/Tb ratio. The compound with [Pr] = 0.15 does not follow this trend.…”
Section: Resultsmentioning
confidence: 99%
“…These values are in good agreement with literature values for small polaron migration in other ceria systems. 19,49,50 The pre-exponential factors show a decreasing tendency with decreasing Pr/Tb ratio. The compound with [Pr] = 0.15 does not follow this trend.…”
Section: Resultsmentioning
confidence: 99%
“…Small polarons conduct either via a hopping mechanism or by a band mechanism. In the temperature region 300-750 K, small polaron band conduction cannot take place [17], Therefore the only possibility left is conduction via a small polaron hopping mechanism in which the charge carrier mobility increases exponentially with temperature. In this compound, the charge carrier mobility increases with temperature as evidenced by the increase in the thermo-electric power with temperature below 750 K. It is concluded that the conduction in the low temperature region is due to transfer of small polarons from the ions of chromium in different valence states, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into electronic conductivity in CeO 2−x with varying x values show that conductivity is related to the departure from stoichiometry 11 and an important point to note is that in addition to decreasing defect concentrations, increasing defect numbers can also reduce conductivity when increased past a certain threshold. 36 As noted by the authors, this issue could 2015) arise for a number of reasons such as defect interactions, localized electrons repelling one another, and a lack of suitable hopping steps for the polaron (Ce 4+ ions are required). Therefore, regions of particularly high or particularly low defect concentrations are expected to be poor electronic conductors in a polaron-hopping regime.…”
mentioning
confidence: 99%